Desempenho de concretos com aditivo cristalizante expostos a sulfatos - Alysson Santos Resende (2023)
The production of concrete with greater durability is fundamental in the development of sustainable constructions, as it minimizes the need for maintenance, demolition and construction of new structures, thus collaborating with the reduction of carbon emissions. Among the causes of deterioration of concrete structures, the predominant one is related to their resistance capacity against the penetration of aggressive agents. The use of crystalline admixtures and additions that promote the self-healing of the concrete, as well as its mechanical protection with geopolymer based on silicates, aim to keep the absorption of water and aggressive agents at low levels. This work presents a performance evaluation regarding resistance, absorption and mass loss of a reference concrete and concrete added with crystalline admixture and with pozzolanic material replacing 50% of cement, later protected by a geopolymer protection layer, submitted to an aggressive environment acid (2.5% H2SO4) by immersion. Based on the dosage studies, a reference concrete was defined subject to environments with a strong aggressiveness class according to NBR 6118 (ABNT, 2014) with 382 kg/m³ of cement, water/cement ratio of 0.50 and fck equal to 30 MPa. All concretes showed good workability and compressive strength at 28 days above 30 MPa. The reference concrete showed an absorption lower than the recommended 10% for good quality concrete. The use of the crystalline admixture in the concrete reduced the water absorption in comparison with the concrete without the admixture. After exposure to sulfates, carried out by immersion in a sulfuric acid solution for 7 days, the evaluation by visual inspection showed that the concretes presented a lesser degree of loss of cohesion of the cement paste, reduced water absorption and lower loss rates mass in concrete with crystallizing additive. There was an improvement in the performance of concretes with the application of geopolymer protection in terms of absorption and mass loss. The combination of crystalline admixture plus geopolymer protection showed significant reductions, mainly in mass loss. This research demonstrates that the use of crystalline admixtures both in concrete produced with cement without additives and in concrete with the addition of pozzolanic material improves the performance of concrete exposed to sulfates and presents even better results when used in conjunction with a geopolymer protective layer.